Patient engagement in the design of a randomised trial of proton beam radiotherapy versus photon radiotherapy for good prognosis glioma. (12th October 2019) - Powell, James R; Murray, Louise; Burnet, Neil; Fernandez, Sharon; McParland, Lucy; O'Hara, Daniel; Lingard, Zoe; Whitfield, Gillian; Short, Susan C
Abstract: Introduction: UK Neuro-Oncologists and multidisciplinary colleagues are developing one of the first randomised clinical trials of proton beam radiotherapy(PBT) to compare quality of life(QOL), cognitive function and other late effects in adults with good prognosis glioma following either PBT or photon radiotherapy. The feasibility of running randomised studies with PBT is an important consideration, particularly in respect of participants' views of a randomised design requiring treatment at national centres. We sought patient and carer engagement on our proposals to ensure we incorporate their views. Methods: To explore these issues, we invited patients who had previously completed radiotherapy for oligodendroglioma and their carers to attend a focus group in Manchester in November 2018. Fifteen participants attended. We sought views on our trial proposal through small group discussions centred around 5 questions, led and facilitated by neuro-oncologists, a research radiographer, neuro-psychologist and statistician. Results: Participants strongly endorsed the trial proposal and positively highlighted the opportunity to access PBT within a clinical trial and the group recognised and supported the need for randomisation and stated this should be 1:1. Patients disliked some traditional terminology such as 'trial' and 'neurocognitive tests' and preferred 'research study' and 'neurocognitive assessments'. Patient and carers expressed the need for careful consideration of issues around travel and accommodation during PBT away from home. Interestingly, participants considered that standard QOL questionnaires fail to address some important areas reflecting daily wellbeing. Conclusion: We acknowledge and will now incorporate these important patient and carer observations to strengthen our study and add validity to the key study endpoints.